Consequences of eutrophication in the management of water resources in Mediterranean reservoirs: A case study of Lake Cedrino (Sardinia, Italy) - Sechi, N. (2020)
The aim of this study was to investigate possible management actions to control eutrophication and assure water use of a eutrophic deep Mediterranean climate reservoir, dominated by cyanobacteria. With this goal, we defined the trophic state of Lake Cedrino (Sardinia, Italy) and studied its phytoplankton, paying particular attention to cyanobacteria, and to seasonal variation of phytoplankton in relation to seasonal variation of environmental variables. On the base of lake features, we propose management actions at different scales and levels to resolve eutrophication and to allow water use: from nutrient load reduction in the watershed (primarily from point-sources) to deep water aeration, to immediately face an attenuation of eutrophic effects. This study is the first explorative step in planning restoration of Lake Cedrino.